Enhanced Near‐Bandgap Response in InP Nanopillar Solar Cells. Issue 10 (24th March 2014) - Battaglia, Corsin; Xu, Jingsan; Zheng, Maxwell; Yin, Xingtian; Hettick, Mark; Chen, Kevin; Haegel, Nancy; Javey, Ali
<x xml:space="preserve">Abstract</x> The effect of nanopillar texturing on the performance of InP solar cells is investigated. Maskless, lithography‐free reactive ion etching of InP nanopillars improves the open‐circuit voltage, reduces reflectance over a broad spectral range, and enhances the near‐bandgap response compared to a flat, non‐textured cell with comparable reflectance in the infrared. Electron‐beam induced current measurements indicate an increased effective minority carrier collection length. The response at short wavelengths decreases due to the formation of a defective surface layer with strong non‐radiative recombination. Plasma oxidation and wet etching partially restore the blue response resulting in a power conversion efficiency of 14.4%.